PRAWO RZYMSKIE A EUROPEJSKA TRADYCJA PRAWNA - Kabat-Rudnicka, Danuta (Zeszyty Prawnicze, 2016)
<!–[if gte mso 9]> <![endif]–> ROMAN LAW AND EUROPEAN LEGAL CULTURE Summary The Roman law and the later neo-Roman law (ius commune), underlies the legal systems of the Western world, i.e. the continental system (civil law) and the Anglo-American system (common law). The essential constants of European legal culture, formed also by the Roman law are: personalism, referring to the individual as subject, end and an intellectual point of reference in the law; legalism, meaning not merely the monopoly of the modern legislator to create and change the law, but the need to base decisions about social relationships and conflicts on a general rule of law, whose validity and acceptance does not depend on moral, social and political values or purposes; intellectualism that relates to the particular way in which the phenomenon of law is understood. And even today, when we observe a trend towards the unification of law, whether on global or only a regional scale, the Roman law can still serve as a point of reference. <!–[if gte mso 9]> Normal 0 21 false false false PL X-NONE HI <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>